Managers’ leadership style and the commitment of their team members: associating concepts in search of possible relations - da Silva, Priscila Lopes; Nunes, Simone Costa; Andrade, Darly Fernando (Review of Business Management, 2019)
Purpose – The aim of the research was to investigate how managers’ leadership styles interfere with the commitment of their team members. Five hypotheses were tested in order to identify relationships between the leadership style and the components of the commitment. Design/methodology/approach – The method chosen was quantitative and a survey was conducted. The data were collected through the application of two questionnaires. A total of 587 questionnaires were considered valid. Descriptive statistics, CHAID analysis and Pearson’s correlation were used in the analysis. Findings – The correlation between the managers’ leadership styles with relationship orientation and the affiliate component of commitment was significant; there is a positive relationship between the task orientation and the normative commitment; there is a positive relation between situational leadership style and affective commitment, as well as between this style and the general commitment. Originality/value – This study contributes to the debate about the existence of a relationship between some components of commitment and leadership styles, pointing out how the leadership style can affect the type of commitment of the team members, specifically regarding the positive relation between the situational leadership style and the general commitment; the relationship orientation and the affiliate component; and the task orientation and normative component.